Pharmacognostic and Physico-chemical Investigation of Barleria cristata Linn. (Leaf) for Quality Control Assessment - Bhuwan Chandra Joshi; Neha Panthri; Nondita Prasad; Jaswinder Kaur Virk (Mazandaran University of Medical Sciences, 2021)
Background: Barleria cristata Linn. belongs to the family Acanthaceae and is commonly known as Raktajhinti and VajraDanti. It is widely distributed in countries, such as India, Nepal, Bangladesh, Pakistan, and Asian tropical regions. This plant has been observed to bear multifarious ethnomedical uses in treating lung disorders, inflammatory conditions, toothache, anemia, and snakebite. A wide range of major chemical constituents, such as triterpenes, phenolic compounds, flavonoids, and glycosides are reported to be present in this plant. The plant exhibited diverse pharmacological actions, such as anti-inflammatory, antibacterial, antifungal, and antioxidant activities. The literature revealed insufficient information concerning the standardization of Barleria cristata Linn. Objectives: The present study aimed to explore the pharmacognostic and phytochemical characteristics of Barleria cristata Linn. (leaf). Methods: The present study addressed quality control parameters, including loss on drying, ash values, extractive values, pharmacognostic parameters (e.g. macroscopic & microscopic characters and powder microscopy) as per the World Health Organization (WHO) guidelines. Results: Biochemical analysis revealed total ash (16.11±0.38), acid insoluble ash (1.50±0.18), water-soluble ash (11.10±0.23), alcohol-soluble extractive (19.34±0.79), and water-soluble extractive (25.06±0.17), respectively. The transverse section of the leaf revealed the presence of the epidermis, covering trichomes, vascular bundle, and so on. The other parameters such as phytochemical investigation, fluorescence analysis, and thin-layer chromatography were also performed to explore the crucial values of these examinations. Conclusion: The obtained data would be useful in the future for preparing a monograph for the authentication and standardization of this crude drug.